2013
DOI: 10.1111/pme.12264
|View full text |Cite
|
Sign up to set email alerts
|

State of the Field Survey: Spinal Cord Stimulator Use by Academic Pain Medicine Practices

Abstract: Standardized SCS training is imperative as the implementation of neuromodulation therapy continues to increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 25 publications
1
37
0
1
Order By: Relevance
“…For instance, 7.5% of current fellows did not perform any SCS implant procedures, while 22.5% participated in over 15. This lack of training uniformity is consistent with the findings of Gharibo et al ,7 who showed large discrepancies in procedure volume at academic institutions. Fanciullo et al 6 also demonstrated a high degree of variability in neuromodulation practice habits at academic institutions, including the length of SCS trials, implantation techniques, opioid weaning and programming algorithms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For instance, 7.5% of current fellows did not perform any SCS implant procedures, while 22.5% participated in over 15. This lack of training uniformity is consistent with the findings of Gharibo et al ,7 who showed large discrepancies in procedure volume at academic institutions. Fanciullo et al 6 also demonstrated a high degree of variability in neuromodulation practice habits at academic institutions, including the length of SCS trials, implantation techniques, opioid weaning and programming algorithms.…”
Section: Discussionsupporting
confidence: 91%
“…Although industry-sponsored training programs could bias the treatment of chronic pain states and the selection of these technologies, Gharibo et al 7 demonstrated a paradigm shift in fellowship education with less programs directors viewing manufacturer involvement negatively. Training courses sponsored by four major SCS manufacturers (Boston Scientific, Medtronic, St. Jude/Abbott and Nevro) at the time of this study were widely attended by both current and past fellows, thereby providing exposure to most of the available neuromodulation technologies in the current marketplace.…”
Section: Discussionmentioning
confidence: 99%
“…ACGME programs in the United States are not without challenge. Recent surveys suggest a lack of neurostimulation exposure , well under the ten cases recommended for primary implanters, and neurostimulation is not a requirement for completion of the fellowship. Thus, variability of existing trainees’ skill sets will continue.…”
Section: Intraoperative Risk Reductionmentioning
confidence: 99%
“…8 Lead migration is a common problem leading to early complications, as recent studies have identified a prevalence of 13–22% of migrations occuring. 11,17 Early interventions to reduce this complication included the advent of multi-contact electrode arrays, along with percutaneous and laminotomy-guided lead placement; while migration rates lowered after these advances, the problem still persists.…”
Section: Discussionmentioning
confidence: 99%
“…7 Nearly 14,000 patients undergo implantation of SCS devices annually for conditions such as complex regional pain syndrome (CRPS), failed back surgery syndrome (FBSS), and ischemic leg pain. 8 SCS has been shown to reduce overall healthcare costs otherwise associated with neuropathic pain due to decreased requirement for narcotic consumption and hospital visits. 9 Recent studies have explored the complication profile associated with SCS, reporting mechanical complications (i.e.…”
Section: Introductionmentioning
confidence: 99%